Bulgaria after liberation: the first steps in the formation of statehood and the role of the Russian Empire in this process (late 1876 – middle 1879) - Vartanyan, Egnara G. (Journal of the Belarusian State University. History, 2025)
The article highlights the role of the Russian Empire in the formation of the Bulgarian statehood after the country’s liberation from Ottoman rule in 1878. Based on documentary sources (archive materials and published documents), the place of the Russian Empire in the process of formation of the Principality of Bulgaria and its main institutions is established. Historical-genetic and problem-chronological methods are used to identify the sequence of historical events; comparative and systemic analysis methods are also used. It is shown that even before the start of the Russo-Turkish War of 1877–1878, the Chancellery of Civil Administration of the Liberated Territories was formed under the Commander-in-Chief of the Danube Army, the purpose of which was to create local government bodies. The article examines the formation of the administrative apparatus in the territories liberated as a result of the war, headed by the Russian Imperial Commissar. It is emphasised that due to the short duration of the Russian administration’s stay in Bulgaria, it was necessary to try to strengthen the country’s independence in the shortest possible time, train personnel from the local population and appoint representatives of the Bulgarian intelligentsia to important administrative posts. The correspondence of Russian government officials, which shows that in a short time the Russian civil administration in Bulgaria accomplished a great deal of work (facilitated the adoption of the country’s constitution, the introduction of tax legislation, the creation of legislative, executive and judicial authorities, the Bulgarian People’s Bank, a new military and police system, a public education system, health care, postal administration and much of what was necessary for the functioning of the revived Bulgarian state), is analysed.
Keywords: Principality of Bulgaria; Russian Empire; liberation; Treaty of San Stefano; Congress of Berlin; constitution; civil administration